CYTOMEGALOVIRUS INFECTION - Nematov H. A.; Bakhronov J. J. (Web of Journals Publishing, 2024)
Cytomegalovirus infection is a widespread human infection with a different transmission mechanism. The variety of clinical manifestations of the disease is due to the ability of human cytomegalovirus to infect almost all cells of the body. Cytomegalovirus often affects people with an immunodeficiency condition. The consequence of this is the continued growth of cytomegalovirus infection not only among children, but also among adults. Cytomegaly is included in the group of "new and mysterious" infections by the WHO Regional Office for Europe.
Keywords: Cytomegalovirus infection, lymphohistiocytic infiltration, cytomegals, localized form, cystic fibrosis, sialoadenitis, hemotransfusion, incomplete replication.